PROBLEMS IN TRANSLATING ENGLISH BIOLOGY TEXTS INTO INDONESIAN - Nasir, Muhamad (2007)
This study intended to investigate the participants' methods, strategies and problems in translating English biology texts. The texts were taken from Campbell's book and Taiz & Zeiger's book consisting of two different branches of Biology namely Plant Development and Animal Development. The study involved three Biology Education students of Graduate School as the participants.The study employed a case study design. The data were obtained from participants' translations and interviews. The translated texts and interviews were then analyzed based on the translation methods drawn from Newmark (1984) and the analyses of translation strategies adopted the strategies from Lam (1995).In addition, the analyses of the translation problems were to do with equivalence, vocabulary and grammatical problems.The findings of the study showed that the participants tended to employ different methods of translation particularly communicative, literal, word for word and free translation methods.By using communicative translation method,the participants in general were able to convey the intended messages of the texts and translated most part of the texts accurately. Meanwhile, by employing the three other methods, they lost the meanings of the source texts, made unnatural translations and failed to deliver messages accurately.With respect to the problems the participants encountered in the translation process were among others; equivalence, vocabulary and grammatical problems. These problems have led them to produce inappropriate translations in some parts of the texts. To cope with these problems, they used various strategies; segmentation strategy, searching strategy, retrieval strategy, and target monitoring strategy.